2020
DOI: 10.3892/ijmm.2020.4676
|View full text |Cite
|
Sign up to set email alerts
|

Nitrodi thermal water downregulates protein S‑nitrosylation in RKO cells

Abstract: Balneotherapy and spa therapy have been used in the treatment of ailments since time immemorial. Moreover, there is evidence to suggest that the beneficial effects of thermal water continue for months following the completion of treatment. The mechanisms through which thermal water exerts its healing effects remain unknown. Both balneological and hydroponic therapy at 'the oldest spa in the world', namely, the Nitrodi spring on the Island of Ischia (Southern Italy) are effective in a number of diseases and con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 46 publications
1
3
0
Order By: Relevance
“…The main components found were chloride (Cl − ) with a mean value of 93 mg/L, sulfates (SO 4 2− ) with a mean value of 204 mg/L, sodium (Na + ) with a mean value of 174 mg/L, and calcium (Ca 2+ ) with a mean value of 137 mg/L. These results obtained were comparable with those reported by Aversano, [ 27 ], which indicated an amount of 0.2200 g/L (220 mg/L), 0.1676 g/L (167.6 mg/L), and 0.1182 g/L (118.2 mg/L), for SO 4 2− , Na + , and Ca 2+ , respectively. However, the HCO 3 − concentration obtained in this study (561 mg/L) was higher than that reported by Aversano (475.8 mg/L).…”
Section: Resultssupporting
confidence: 88%
“…The main components found were chloride (Cl − ) with a mean value of 93 mg/L, sulfates (SO 4 2− ) with a mean value of 204 mg/L, sodium (Na + ) with a mean value of 174 mg/L, and calcium (Ca 2+ ) with a mean value of 137 mg/L. These results obtained were comparable with those reported by Aversano, [ 27 ], which indicated an amount of 0.2200 g/L (220 mg/L), 0.1676 g/L (167.6 mg/L), and 0.1182 g/L (118.2 mg/L), for SO 4 2− , Na + , and Ca 2+ , respectively. However, the HCO 3 − concentration obtained in this study (561 mg/L) was higher than that reported by Aversano (475.8 mg/L).…”
Section: Resultssupporting
confidence: 88%
“…Firstly, the phenomenon of S-nitrosylation, understood as the addition of nitric oxide (NO) to the thiol side chain of cysteine residues within proteins, has been the subject of a lot of academic interest. The aberrant S-nitrosylation of proteins is associated with many diseases [ 61 ]. NO is also a key messenger in the pathogenesis of inflammation and exerts this effect by activating innate and adaptive immunity.…”
Section: Beneficial Effects Of Nitrodi’s Water: Ongoing Datamentioning
confidence: 99%
“…The results obtained from these experiments showed that MMP-2 protein expression and protein S-nitrosylation were markedly downregulated in RKO cells treated with Nitrodi’s water. Overall, the results revealed that the molecular mechanisms through which Nitrodi’s spring water exerts its anti-inflammatory effects might involve the downregulation of protein S-nitrosylation [ 61 ].…”
Section: Beneficial Effects Of Nitrodi’s Water: Ongoing Datamentioning
confidence: 99%
“…These results represent early evidence that sulphur-based compounds may be useful in treating chronic in ammatory ailments, despite the mechanism remaining unknown. More recently, Aversano et al reported that a thermal mineral water showed an in-vitro anti-in ammatory activity by down-modulating cyclooxygenase (COX)-2 and matrix metallopeptidase (MMP) 2 proteins (Aversano et al 2020). In ammation is an important step of wound healing and begins after injury.…”
Section: Introductionmentioning
confidence: 99%